The Demand for Interns - David A. Jaeger; John M. Nunley; Jr. Seals; Eric J. Wilbrandt (Institute of Labor Economics (IZA), 2020)
We describe the demand for interns in the U.S. using ads from an internship-specific website. We find that internships are more likely to be paid when more closely associated with a specific occupation, when the local labor market has lower unemployment, and when the local and federal minimum wage are the same. A résumé audit study with more than 11,500 applications reveals that employers are more likely to respond positively when internship applicants have previous internship experience. Employers are also less likely to respond to applicants with black-sounding names and when the applicant is more distant from the firm.
Keywords: J23; I23; 330; internships; training; audit study